The cystine/glutamate antiporter system xc− drives breast tumor cell glutamate release and cancer-induced bone pain. Issue 11 (November 2016) - Slosky, Lauren M.; BassiriRad, Neemah M.; Symons, Ashley M.; Thompson, Michelle; Doyle, Timothy; Forte, Brittany L.; Staatz, William D.; Bui, Lynn; Neumann, William L.; Mantyh, Patrick W.; Salvemini, Daniela; Largent-Milnes, Tally M.; et al.
Abstract : Abstract: Bone is one of the leading sites of metastasis for frequently diagnosed malignancies, including those arising in the breast, prostate and lung. Although these cancers develop unnoticed and are painless in their primary sites, bone metastases result in debilitating pain. Deeper investigation of this pain may reveal etiology and lead to early cancer detection. Cancer-induced bone pain (CIBP) is inadequately managed with current standard-of-care analgesics and dramatically diminishes patient quality of life. While CIBP etiology is multifaceted, elevated levels of glutamate, an excitatory neurotransmitter, in the bone-tumor microenvironment may drive maladaptive nociceptive signaling. Here, we establish a relationship between the reactive nitrogen species peroxynitrite, tumor-derived glutamate, and CIBP. In vitro and in a syngeneic in vivo model of breast CIBP, murine mammary adenocarcinoma cells significantly elevated glutamate via the cystine/glutamate antiporter system xc − . The well-known system xc − inhibitor sulfasalazine significantly reduced levels of glutamate and attenuated CIBP-associated flinching and guarding behaviors. Peroxynitrite, a highly reactive species produced in tumors, significantly increased system xc − functional expression and tumor cell glutamate release. Scavenging peroxynitrite with the iron and mangano-based porphyrins, FeTMPyP and SRI10, significantly diminished tumor cell system xc − functional expression, reduced femur glutamate levels and mitigated CIBP. In sum, we demonstrate how breast cancer bone metastases upregulate a cystine/glutamate co-transporter to elevate extracellular glutamate. Pharmacological manipulation of peroxynitrite or system xc − attenuates CIBP, supporting a role for tumor-derived glutamate in CIBP and validating the targeting of system xc − as a novel therapeutic strategy for the management of metastatic bone pain. Abstract : Supplemental Digital Content is Available in the Text.Tumor-derived glutamate may significantly contribute to cancer-induced bone pain. The glutamate transporter system xc − is a promising therapeutic target in this pain state.